The antimicrobial activity of some medical plants against bacteria that cause urinary tract infection - Nehia hussein; noor ameer hanon (Al-Mustansiriyah Journal of Science)
This study was done to evaluate the antibacterial activity of hot ethanolic and aqueous extracts of Syzygium aromatic (S.aromatic ) and Q.infectoria infectoria (gall) against pathogenic bacteria that cause urinary tract infection (UTI). Such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Qualitative detection of the active compounds of the plant extracts was done with chemical reagents. Also, the Qualitative detection of the active groups was further verified with (FTIR). The sensitivity of the UTI causing bacteria was examined against 12 different antibiotics. The results show that E.coli was the most resistant bacteria, resisting 8 from 12 antibiotics; P.aeruginosa resisted 5 from 12 antibiotics; while S.aureus showed resistance to 4 only. The antibacterial activity of the plant extracts was investigated by using four concentrations (40, 60, 80, 100 mg/ml) for each extract against two types of Gram negative bacteria (E.coli, P.aeruginosa), and one type of Gram-positive bacteria (S. aureus). The plant extracts showed different effects on the growth of all bacterial strains. The Minimum Inhibitory Concentration (MIC) and the Minimum bactericidal concentration (MBC) of the ethanolic extracts and aqueous extracts in the study were determined.The kill- time was determined also for each extract.The antioxidant activity of the plants in the study was investigated. Finally, the toxicity of the plant extracts was examined on human red blood cells.